Suitability of Different PCR-DGGE Primer Sets for the Monitoring of Lactic Acid Bacteria in Wine - Mayrhofer, S.; Filipp, R.; Lehner, D.; Reiterich, C.; Kneifel, W.; Domig, K.J. (South African Journal of Enology and Viticulture, 2016)
Lactic acid bacteria (LAB) play a dual role in winemaking as they are the main effectors of malolactic fermentation, but some members can also cause wine spoilage. PCR-DGGE has proved to be a quick tool to study the LAB community and their fluctuation in wine. For detecting wine-associated LAB by PCR-DGGE, the primer sets WLAB1/WLAB2GC, WBAC1/WBAC2GC, Lac1/Lac1o/Lac2GC, 341fGC/518r and rpoB1/rpoB1o/rpoB2GC were tested and evaluated in this study. The primer systems were assessed by the separation of LAB reference strains on DGGE gels and by attributing the resulting amplicons to defined species. Subsequently, the detection of LAB in wine samples and enrichments thereof was compared. While the primer systems WBAC1/WBAC2GC and 341fGC/518r were not appropriate, the Lac1/Lac1o/Lac2GC primer set performed well. However, multiple bands complicated the evaluation. The rpoB1/rpoB1o/rpoB2GC set seemed to be promising for the detection of LAB in wine, although further improvements in terms of the detection limit need to be done. Due to the pronounced sensitivity and the sufficient discrimination of LAB at species level, the WLAB1/WLAB2GC primer system was found to be most suitable for studying the occurrence of LAB in wine.